Nikonion in Roman Times. A Fragment of History of an Ancient City on the Lower Dniester - Mielczarek, Mariusz (Acta Archaeologica Lodziensia, 2021)
This article presents settlement during the Roman period upon the territory of the Greek city of Nikonion, which developed on the mouth of the Dniester River from the 6th century BC to the middle of the 3rd century BC. The region was brought into the Roman sphere of interest in the 1st century AD. The middle of the 1st century AD was the time of the repeated settlement of the Greek city. The basis for these speculations are materials obtained during archaeological work carried out by the Archaeological Museum of the Ukrainian Academy of Sciences in Odessa as well as the Institute of Archaeology of the N. Copernicus University in Toruń and the Institute of Archaeology and Ethnology of the Polish Academy of Sciences